Altitude training considerations for the winter sport athlete - Chapman, R. F.; Stickford, J. L.; Levine, B. D. (Experimental Physiology, 2010)
Winter sports events routinely take place at low to moderate altitudes, and nearly all Winter Olympic Games have had at least one venue at an altitude >1000 m. The acute and chronic effects of altitude can have a substantial effect on performance outcomes. Acutely, the decline in oxygen delivery to working muscle decreases maximal oxygen uptake, negatively affecting performance in endurance events, such as cross-country skiing and biathlon. The reduction in air resistance at altitude can dramatically affect sports involving high velocities and technical skill components, such as ski jumping, speed skating, figure skating and ice hockey. Dissociation between velocity and sensations usually associated with work intensity (ventilation, metabolic signals in skeletal muscle and heart rate) may impair pacing strategy and make it difficult to determine optimal race pace. For competitions taking place at altitude, a number of strategies may be useful, depending on the altitude of residence of the athlete and ultimate competition altitude, as follows. First, allow extra time and practice (how much is yet undetermined) for athletes to adjust to the changes in projectile motion; hockey, shooting, figure skating and ski jumping may be particularly affected. These considerations apply equally in the reverse direction; that is, for athletes practising at altitude but competing at sea level. Second, allow time for acclimatization for endurance sports: 3-5 days if possible, especially for low altitude (500-2000 m); 1-2 weeks for moderate altitude (2000-3000 m); and at least 2 weeks if possible for high altitude (>3000 m). Third, increase exercise-recovery ratios as much as possible, with 1:3 ratio probably optimal, and consider more frequent substitutions for sports where this is allowed, such as ice hockey. Fourth, consider the use of supplemental O2 on the sideline (ice hockey) or in between heats (skating and Alpine skiing) to facilitate recovery. For competitions at sea level, the `live high-train low' model of altitude training can help athletes in endurance events to maximize performance.